Strategi Komunikasi Pemasaran K-Radio Jember dalam Mendapatkan Iklan - Setiawan, Moh. Basori; Ainul Yaqin , Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2024)
Radio is a medium that can only be heard and played once. In this digital era, radio is required to be able to develop and coexist with the internet era or the modern era. Currently, the internet makes it easier for people to obtain music, entertainment and information. Such as from Facebook, Twitter, Tiktok, Instagram, YouTube and other social media platforms. Therefore, radio must be able to maintain its existe bangghostmen@gmail.com, gusainul@gmail.com nce in the current digital era for the future of radio so that it remains standing and carries out operational activities every day. K-Radio maintains its existence by developing multiplatform. Researchers are interested in this radio because they want to explain the marketing communication strategies implemented by K-Radio in obtaining advertising. Therefore, the researcher raised this as the focus of the research. This research uses a qualitative method with a descriptive approach. This research aims to analyze and explain the marketing communication strategies used by K-Radio Jember in obtaining advertisements. The data collection techniques used were observation, interviews and documentation. The results of this research show that K-Radio Jember implements a marketing strategy by applying the concept of Experience and One Stop Shopping, Data and Portfolio, K-Radio Branding, Content Creativity on Multiplatform, and Promotions and Events. In the implementation process, the marketing communications strategy implemented by K-Radio Jember turned out to have several challenges, but these challenges can be overcome by developing multi-platforms and creating creativity and innovation in broadcast content and social media content